A comparative evaluation of medicine package inserts for oral antidiabetic agents in Palestine - Malak Eshtayeh; Asia Draghmeh; Sa'ed H. Zyoud (BMC, 2019)
Abstract Background Patient package inserts (PPIs) should provide accurate, sufficient, and clear information for patients as well as health care professionals. The goal of this study was to evaluate and compare the PPIs of local and imported anti-diabetic agents in the Palestinian market. Methods Eighteen leaflets were collected and analysed based on the completeness of 31 criteria using a scoring method, then the quantity of information was assessed by applying word counting of 17 headings and subheadings. Statistical comparisons of the word count for all products were performed using the Mann-Whitney U test with mean ranks. Then the mean ranks for differences in word counts were adjusted to calculate the fold-difference statistic by dividing the higher mean rank by the lower mean rank. Results In general, the PPIs of imported agents scored better than local PPIs, but none of the inserts fulfilled the whole criteria. Thirteen out of thirty-one criteria were available in all products. None of these agents had provided any information about duration of use, instructions to convert tablets into liquids forms, pharmacokinetics, or shelf life. Moreover, mechanism of action and maximum dose were deficient in all local PPIs (0.0%), while they were included in 37.5 and 62.5% of imported PPIs, respectively. Furthermore, 90.0% of local PPIs lacked information about drug dose, 80.0% didn't mention any instructions regarding effects on ability to drive or possibility of tablet splitting, and 60.0% didn't involve orders about possibility of tablet crushing. Local PPIs provided inadequate and less detailed instructions regarding many aspects, since the estimated mean rank of local and imported PPIs demonstrated a range of difference from 1.04-fold for missing dose to 2.64-fold for warning and precautions. Conclusions Significant differences were being identified, with excellence being assigned to imported PPIs. So, it is worth suggesting some necessary modifications in PPI topography and sequence structure of local diabetic agents. Experts in Palestinian Ministry of Health should implement regulatory guidelines to improve the quality and quantity of information provided by local PPIs. This optimisation could become a step forward toward optimal health practice in our society.